2022
DOI: 10.3390/insects13080749
|View full text |Cite
|
Sign up to set email alerts
|

New Records and Updated Checklist of the Pentatomoidea (Hemiptera: Heteroptera) of Greece

Abstract: Eight species of the superfamily Pentatomoidea are recorded from Greece for the first time: Aelia germari Küster 1852, Eurygaster hottentotta (Fabricius 1775), Eysarcoris aeneus (Scopoli 1763), Neottiglossa lineolata (Herrich-Schaeffer 1830), Neottiglossa pusilla (Gallen 1789), Picromerus bidens (Linnaeus 1758), Podops (Podops) inunctus (Fabricius 1775) and Tarisa pallescens (Jakovlev 1871). A complete updated species checklist with distributional data notes for all the new species for Greece are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Investigation on life history of shield bugs till now found that most species of them overwinter in diapause as adults ( Hodek and Hodkova 1993 , Šlachta et al 2002 , Santos et al 2003 , Robert et al 2021 ). Dolycoris baccarum (L.) (Heteroptera: Pentatomidae) is widely distributed throughout the Asian and European continents, where it feeds on many species of plants and harms numerous crops, such as soybeans, cotton, sesame, carrots, burdock, wheat, tobacco, and rice ( Fent and Aktaç 1999 , Tsagkarakis et al 2022 ). In China, it is widely distributed from provinces in the south to Inner Mongolia, Xinjiang, and Heilongjiang in the north ( Sachurula et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Investigation on life history of shield bugs till now found that most species of them overwinter in diapause as adults ( Hodek and Hodkova 1993 , Šlachta et al 2002 , Santos et al 2003 , Robert et al 2021 ). Dolycoris baccarum (L.) (Heteroptera: Pentatomidae) is widely distributed throughout the Asian and European continents, where it feeds on many species of plants and harms numerous crops, such as soybeans, cotton, sesame, carrots, burdock, wheat, tobacco, and rice ( Fent and Aktaç 1999 , Tsagkarakis et al 2022 ). In China, it is widely distributed from provinces in the south to Inner Mongolia, Xinjiang, and Heilongjiang in the north ( Sachurula et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%